CX3CL1 Induces Vertebral Microvascular Barrier Dysfunction via the Src/P115-RhoGEF/ROCK Signaling Pathway - Yi, Lei; Liang, Yun; Zhao, Quanming; Wang, Houlei; Dong, Jian (Frontiers in Cellular Neuroscience, 2020)
Trans-endothelial migration (TEM) of cancer cells is a critical step in metastasis. Micro-vascular barrier disruptions of distant organs play important roles in tumor cells TEM. The spine is a preferred site for multiple cancer cell metastases. Our previous study found that vertebral spongy bone was rich in CX3CL1 and that CX3CL1 can attract fractalkine receptor-expressing tumor cells to the spine. In the present study, we determined whether CX3CL1 was involved in vertebral micro-vascular barrier disruption and promoted tumor cell TEM after circulating tumor cells were arrested in the vertebral micro-vasculature. We examined the role of CX3CL1 in the barrier function of vertebral micro-vascular endothelial cells (VMECs) and explored the molecular mechanisms of CX3CL1-induced VMEC barrier disruption. Our results demonstrated that CX3CL1 led to F-actin formation and ZO-1 disruption in VMECs and induced the vertebral micro-vascular barrier disruption. Importantly, we found that the activation of the Src/P115-RhoGEF/ROCK signaling pathway plays an important role in CX3CL1-induced VMEC stress fiber formation, ZO-1 disruption and then vertebral micro-vascular barrier hyper-permeability. Inhibiting Src/P115-RhoGEF/ROCK signaling in VMECs effectively blocked CX3CL1-induced vertebral vascular endothelial dysfunction and subsequent tumor cell TEM. The results of this study and our previous study indicate that in addition to its chemotaxis, CX3CL1 plays a critical role in regulating vertebral micro-vascular barrier function and tumor cell TEM. CX3CL1 induced VMECs stress fiber formation, ZO-1 disruption and then vascular endothelial hyperpermeability via activation of the Src/P115-RhoGEF/ROCK signaling pathway. The inhibition of the Src/P115-RhoGEF/ROCK signaling pathway in VMECs effectively blocked tumor cells TEMs in vertebral spongy bone and maybe a potential therapeutic strategy for spine metastases in the future.